DEEP LEARNING CURRICULUM STRATEGIES TO FOSTER CRITICAL THINKING IN EARLY YEARS - Hibana; Eka Putri Sulistia Hutabarat (El Midad, 2026)
This study aims to analyze the implementation strategies for a deep-learning pedagogy-based curriculum that fosters young children’s critical thinking skills in Early Childhood Education (ECE). The study employed a qualitative, descriptive case-study design to obtain an in-depth understanding of curriculum implementation processes. Data were collected through classroom observations, in-depth interviews with school principals and teachers, and documentation analysis of instructional planning and assessment records, and were analyzed using thematic analysis procedures consisting of data reduction, data display, and conclusion drawing. The findings indicate that deep learning-based curriculum implementation was carried out through contextual learning planning, inquiry- and exploration-based learning activities, and authentic assessment oriented toward children’s thinking processes. These strategies stimulated children’s abilities to observe, ask questions, compare objects, and make simple predictions appropriate to their developmental stage. This study contributes to the development of early childhood pedagogy by providing an empirical description of how deep learning pedagogy can be systematically implemented through integrated planning, implementation, and evaluation processes to support children’s cognitive development.